Italian intervention in the Spanish Civil War - Coverdale, John F., 1940- (Princeton, New Jersey : Princeton University Press, 1975)
Using hitherto unavailable material from the Italian foreign ministry, Franco's headquarters, and Mussolini's secretariat, John F. Coverdale traces the development of Italo-Spanish relations from the beginning of the Fascist regime. His analysis reveals that traditional foreign policy outweighed ideological and internal political considerations in Mussolini's decision making. John F. Coverdale finds that while Italy's support was essential to Franco's victory, Rome exercised very little influence on his decisions. The author concludes that participation in the Spanish Civil War was less important than is generally believed in determining Italy's entrance into World War II on Hitler's side, and that it did not significantly weaken her armed forces.Originally published in 1976.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- TABLE OF CONTENTS -- LIST OF TABLES -- LIST OF MAPS -- PREFACE -- ACKNOWLEDGMENTS -- ABBREVIATIONS -- PART I -- ONE. THE BACKGROUND OF INTERVENTION: ITALY IN 1936 -- TWO. THE BACKGROUND OF INTERVENTION: ITALO-SPANISH RELATIONS 1922-1936 -- THREE. THE DECISION TO SUPPORT FRANCO: JULY 1936 -- FOUR. THE INTERNATIONALIZATION OF THE CONFLICT: AUGUST-NOVEMBER 1936 -- FIVE "CONTE ROSSI" IN MAJORCA -- PART II -- SIX. AN ITALIAN ARMY IN SPAIN: DECEMBER 1936-MARCH 1937 -- SEVEN. ITALIAN TROOPS IN ACTION: MALAGA AND GUADALAJARA -- PART III -- EIGHT. INTERNATIONAL TENSION: MARCHSEPTEMBER 1937 -- NINE.TO THE BITTER END: OCTOBER 1937-APRIL1939 -- TEN. EPILOGUE AND CONCLUSIONS -- APPENDICES -- A NOTE ON SOURCES -- INDEX -- Backmatter
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Spain -- History -- Civil War, 1936-1939 -- Participation, Italian; HISTORY -- Europe -- Spain & Portugal; Military participation -- Italian; Spain; 1936-1939; History